MIGRATION AND POPULATION MOVEMENTS IN AFRICA: CAUSES AND DEVELOPMENT IMPLICATIONS - Ochanja Ngara, Christopher; Jonah Udoh, Anietie; Sabina Nwagu, Chigozie (African Journal of Social and Behavioural Sciences, 2026)
Migration and population movements have long characterised human societies, driven by economic, political, social, and environmental conditions. Although migration can promote development through remittances, knowledge transfer, and transnational networks, many African migrants continue to undertake irregular migration under hazardous and exploitative conditions. This paper examined the major determinants of migration and population mobility in Africa and their implications for the continent’s development. It argued that migration is largely shaped by persistent structural inequalities and the socio-economic and political conditions of both origin and destination countries, which create push and pull factors influencing migration decisions. South–North migration remains a significant aspect of Africa’s international migration, particularly among individuals seeking improved employment opportunities, education, and security. The study adopted a descriptive research design, using a documentary (desk review) approach based exclusively on secondary data. Data are drawn from peer-reviewed journal articles, government publications, institutional reports, and datasets from reputable organisations, including the International Organisation for Migration, the United Nations, the United Nations Department of Economic and Social Affairs, the African Union, the World Bank, and the African Development Bank. These sources provide credible evidence for analysing the drivers, patterns, and development implications of migration across Africa. The paper concludes that addressing the root causes of migration requires comprehensive political, economic, and institutional reforms aimed at reducing structural inequalities, expanding employment opportunities, strengthening governance, and promoting inclusive and sustainable development across the continent.